Gender Wage Gap - A Matching Analysis for Three MENA Countries: Egypt, Jordan and Turkey - Ömer Tuğsal Doruk; Francesco Pastore (Institute of Labor Economics (IZA), 2020)
We investigate the gender wage gap in three neglected MENA countries: Egypt (1980-2018), Jordan (2010-2016), and Turkey (2014-21017). We use repeated cross-sections and propensity score matching as the best way to control for observed heterogeneity. We find a much more sizeable gap than in advanced economies, but with a downward trend similar to advanced economies, reaching in Jordan a low of -0.18.
Keywords: C31; J16; J31; K38; 330; gender wage gap; propensity score matching; Turkey; Jordan; Egypt